Exploration of Pulp and Husk of Gayo Arabica Coffee as Raw Material of Pectin – SWOT, Risk and Chemical Component Analysis - Ismail Sulaiman; Murna Muzaifa; Dian Hasni; Julius Munandar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Advances  in  waste  management  offer  huge  possibilities  for  economic  and  social  utilization  of residues from coffee production such as the pulp and husk. Coffee pulp are obtained during coffee production around 20-45% of raw material either it processed wet or dry. In Gayo Highland areas, as  a  centre  of  Arabica  production  in  Indonesia,  coffee  production  known  as  semi-drying  process where  numbers  of  coffee  residues  arise  up  to  40%  of  total  coffee  berries.  For  local  farmers  pulp and  husks  often  be  decompose  by  burning,  whether  several  alternatives  have  been  attempted individually,  either  used  as  fertilizer,  livestock  feed  and  compost.  However  the  applications  above cover  only  small  number  of  robust  coffee  residues.  Therefore  studies  have  been  conducted  to explore  possibility  to  extract  pectin  from  coffee  pulp.  Implementation  of  SWOT  analysis  and  Risk Analysis by FMEA gain to enhance the information of strength, weakness, opportunity and threats of extraction pectin from coffee pulp/husks demonstrated that this attempt have higher possibility to be more efficient than others trial for both economically and ecologically. Furthermore, moisture contents,  ash  and  crude  fiber  are  examined  from  fresh  pulp/husk  which  are  stored  in  room temperatures for 16 days, 24 days and 30 days. The data demonstrated that length of storage up to 30 days has impact on increasing ash (up to 12.66% from 1.38%)  and solid fiber contents (up to  28.24%  from  2.70%)  whilst  moisture  are  decreased  (down  to  15.51%  from  86.08%)  which emphasizes  that  delaying  production  or  prolonging  the  storage  of  coffee  residues  might  not  have any impact on product quality